Attitude Towards Care of Dying Patients among the Interns in a Tertiary Care Hospital (International Journal of Nursing Education, 2019)
Aim: To assess the attitude among interns on palliative care in a tertiary care unit Background: Palliative care is a specialized approach for the terminally ill patients which focuses on relieving the pain and stress of the dying patient and their family. At the end of the curriculum all doctors are capable of treating a patient but the psychological stress while dealing with a dying patient is not balanced properly. Hence our study was designed with the idea to assess the attitude on palliative care by a FATCOD questionnaire. Subjects and Method: A descriptive study conducted among 100 interns from a tertiary care hospital. FATCOD, a standard questionnaire with 30 item tool using a five-point Likert scale is used assess the attitude of health professionals on palliative care. Results: Participants included 52 female interns and 48 males. Mean score of the study population was 92.07 ± 13. Conclusions: We conclude that the awareness on palliative care is low among the interns. This signifies the need for education and awareness about palliative care to medical students